2010
DOI: 10.1002/mus.21869
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of muscle fibrosis and myonecrosis in mdx mice by suramin, a TGF‐β1 blocker

Abstract: Fibrosis is a pathological feature observed in patients with Duchenne muscular dystrophy (DMD) and in mdx mice, the experimental model of DMD. We evaluated the effect of suramin, a transforming growth factor-beta 1 (TGF-β1) blocker, on fibrosis in mdx mice. mdx mice (6 months old) received suramin for 7 weeks. Suramin- and saline-treated (control) mdx mice performed exercise on a treadmill to worsen disease progression. Immunoblotting showed an increase of TGF-β1 in mdx diaphragm, limb, and cardiac muscles. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 39 publications
11
80
0
3
Order By: Relevance
“…Immune system modulation had always been a promising tool to almost delay onset and slow progression of DMD symptoms. To date, steroids are the most effective and utilized treatment, but new immune-modulatory drugs have been experimented to improve muscle repair by reducing inflammation and fibrosis of DMD animal models as anticytokines (anti-TNFα), 30 IL-6r blockade, 31 TGF-β blocker (suramin and pirfenidone) 32,33 and, more recently, Treg expansion. 13 Several evidences suggested that the proteasome is directly involved in the pathophysiology of organ fibrosis: inhibition of the proteasome could block TGF-β1 induced gene expression in primary human lung fibroblasts from healthy individuals and patients with IPF 34,35 and could reduce lung fibrosis in some animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Immune system modulation had always been a promising tool to almost delay onset and slow progression of DMD symptoms. To date, steroids are the most effective and utilized treatment, but new immune-modulatory drugs have been experimented to improve muscle repair by reducing inflammation and fibrosis of DMD animal models as anticytokines (anti-TNFα), 30 IL-6r blockade, 31 TGF-β blocker (suramin and pirfenidone) 32,33 and, more recently, Treg expansion. 13 Several evidences suggested that the proteasome is directly involved in the pathophysiology of organ fibrosis: inhibition of the proteasome could block TGF-β1 induced gene expression in primary human lung fibroblasts from healthy individuals and patients with IPF 34,35 and could reduce lung fibrosis in some animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Western blots were performed as previously described (Taniguti et al, 2011). Briefly, the muscles were lysed in assay lysis buffer (1% Triton, 10 mM sodium pyrophosphate, 100 mM NaF, 10 g/ml aprotinin, 1 mM PMSF and 0.25 mM Na 3 VO).…”
Section: Western Blottingmentioning
confidence: 99%
“…TGF-␤ induces the transformation of fibroblasts into myofibroblasts, which extensively promote fibrosis by secreting collagens and fibronectin (Barnes and Gorin, 2011). Inhibition of the TGF-␤ signal and inflammatory response is a therapeutic strategy for DMD (Huang et al, 2009;Taniguti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%